Epitope-Specific Antibody Levels in Tuberculosis: Biomarkers of Protection, Disease, and Response to Treatment - Bothamley, Graham H. (Frontiers in Immunology, 2014)
Monoclonal antibodies restricted to Mycobacterium tuberculosis can measure epitope-specific antibody levels in a competition assay. Immunodominant epitopes were defined from clinical samples and related to the clinical spectrum of disease. Antibody to the immunodominant epitopes was associated with HLA-DR15. Occupational exposure showed a different response and was consistent with recognition of dormancy related proteins and protection despite exposure to tuberculosis. Studies in leprosy revealed the importance of immune deviation and the relationships between T and B cell epitopes. During treatment, antibody levels increased, epitope spreading occurred, but the affinity constants remained the same after further antigen exposure, suggesting constraints on the process of epitope selection. Epitope-specific antibody levels have a potential role as biomarkers for new vaccines which might prevent the progression of latent to active tuberculosis and as tools to measure treatment effects on subpopulations of tubercle bacilli.